The mediating effect of perceived usefulness towards tax service quality and the continuance usage intention of the filing system in Malaysia - Santhanamery, T.; Ramayah, T. (2015)
This study examines the mediating effect of perceived usefulness on the relationship between tax service quality (correctness, response time, system support) and continuance usage intention of e-filing system in Malaysia. A total of 116 data was analysed using Partial Least Squared Method (PLS). The result showed that Perceived Usefulness has a partial mediating effect on the relationship between tax service quality (Correctness, Response Time) with the continuance usage intention and tax service quality (correctness) has significant positive relationship with continuance usage intention. Perceived usefulness was found to be the most important predictor of continuance usage intention